Factors Associated with Relapse in Men with Alcohol Dependence Versus Opioid Dependence: A Comparative Study From Western Nepal - Khan, Tanveer Ahmed; Dutta, Ashish; Subedi, Sandip (Journal of Nepalgunj Medical College, 2018)
Introduction: Drug abuse is a worldwide problem that affects millions of people and Nepal is no exception. Relapse is a major problem in management of substance use disorder. Hence it becomes important to understand the factors contributing to relapse in order to ensure relapse prevention. This study was done with the aim to compare clinico-demographic correlates of relapse in alcohol dependence and opioid dependence and also to know the reasons for relapse in both groups.Method: This is a cross sectional comparative study with the sample collected from three different rehabilitation centers from Nepalgunj. The sampleinclude those male clients with alcohol dependence and opioid dependence who had relapsed at least once in past after some period of abstinence. Total of 80 male subjects i.e. 40 in each group were enrolled in the study. Structured questionnaire was developed by the researcher and was used to collect the data from respondents. The data were statistically analyzed.Result: Some clinic-demographic disparity was observed in both groups. Alcohol group had more subjects from Bahun and Chettri caste, longer total duration of illness whereas opioid group had more Muslims, younger age and greater number of middle socio-economic clients, more number of substances used in past and higher prevalence of criminal act. The commonest reason for relapse in both groups found to be desire for positive mood. Peer pressure, social or family problems, craving, negative mood state and concentration difficulties were other factors found to be contributing to relapse. Narcotic Anonymous was the most preferred modality of treatment opted by both groups in past in order to quit substance whereas only 22.5% of subjects consulted to doctor.Conclusion: Social determinants play a critical role in substance use and its relapse and should be addressed alongside physical and psychological determinants for better outcome. Common factors play role for relapse in both groups. Study warrants increased need of mental health awareness programme among substance abusers.